PEMBERIAN PUPUK KANDANG DAN VOLUME AIR TERHADAP PERTUMBUHAN DAN HASIL KEDELAI EDAMAME (Gycine max (L.) Merril) - Miya Ramadhani; Fetmi Silvina; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aim to get the interaction of manure and water volume on the growth and yield of edamame soybean and determine the combination that gives the highest production on the growth and yield of edamame soybean. This research was conducted at the Screen House Stadion of Agriculture Faculty, University of Riau on January 2015 until March 2015. This research arranged Completely Rendomized Design (CRD) with factor (I) composed of three (5 tons/ha, 10 tons/ha, 15 tons/ha) and factor (II) composed of three  (50% water volume, 75% water volume, 100% water volume). The data analyzed by (ANOVA) and tested further by Duncan Multiple Test Level (DNMRT) at 5%. The observed parameters are plant height, days to flowering, percentage of effective root nodules, plant dry weight, number of branches, number of plant pods, percentage filled pods, weight of plant pods, seeds weight a plant and number of seeds a plant. Interaction manure and water volume improve on percentage filled pod and doesn`t improve on plants height, days to flowering, percentage of effective root nodules, plant dry weight, number of branches,number of plant pods, weight of plant pods, seeds weight a plant and number of seeds a plant. Manure 5 tons/ha and 50% water volume is a combination treatment of the highest. Keywords : Edamame Soybean, Manure, Water Volume